OVARIUM ACTIVITIES OF LANDRACE AND BALI SOWS AT TRADITIONAL SLAUGHTER HOUSING - SUMARDANI N. L. G.; I W. SUBERATA; N. M. ARTININGSIH; K. BUDAARSA (Fakultas Peternakan Universitas Udayana, 2018)
The reproductive status of sows can be analyzed based on its level of ovarian activities characterized by thepresence of a number of follicles and corpus luteum in the ovary. The study of level of ovarium activity of sowsobserved the level of other reproductive performance. In this study, 100 ovaries in each 50 Landrace and bali sowswere divided into three groups of sows weighs slaughtering as of 60-70 kg (A); 71-80 kg (B); and 80-90 kg (C). Thevariables observed were dimensions of ovary, the number of follicles and corpus luteum in the right and left ovaries.Quantitative data with quantitative t-test determines the comparison on right and left ovary activities. It showedthat the average weight of right and left ovaries in landrace sows were 5.70 ± 1.22 g; 6.77 ± 0.96 g, and 4.89 ± 1.47g; 6.13 ± 1.46 g in bali sows. The average number of dominant follicles on the right and left ovaries of landrace sowswere 6.54 ± 1.81 f follicles; 9.78 ± 1.58 follicles, and on bali sows is 5.82 ± 1.90 follicles; 8.91 ± 1.50 follicles. Thenumber of corpus luteum on the right and left ovaries of the Landrace were 5.49 ± 2.22 CL; 8.16 ± 1.86 CL, and onbali sows is 5.27 ± 2.23 CL; 7.69 ± 2.22 CL. The t-test results showed that average number of dominant follicles andcorpus luteum in left ovary were significantly greater (P <0.05) compared to the right ovary. The highest percentageof dominant follicles and corpus found in sows of slaughter grouping 80-90 kg (C). It can be concluded that leftovary activity was more active than right ovary, and ovarian activity positively correlated with ovarian weight whichindicating ovarian activity in egg cell production and reproductive hormone.